Strategi Pembelajaran Daring Luring Dalam Upaya Mengatasi Kesulitan Belajar Siswa Pada Masa Pandemi Covid-19 Di Sdn Kramat 3 Kota Magelang - Defi Nadata Putri Rianto (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The existence of cases of learning difficulties experienced by students during the Covid-19pandemic made student less understand the subject matter presented by the teacher. Thisstudy aims to determine the learning strategy of daring to captivate in an effort toovercome student learning difficulties during the COVID-19 pandemic at SDN Kramat 3Magelang City. This research applies a qualitative case study. Data were collected using aquestionnaire from interviews. The sample used in this study was a 4th grade teacher atSDN Kramat 3 Magelang City. The results of this study indicate that learning courageaffects the learning difficulties of grade 4 students at SDN Kramat 3 Magelang City.Keywords: Strategy, Offline Learning.